The Influence of Hybrid Learning Model on The Results of the Design of Fashion Study Design Study Viewed from Creative Levels Thinking Students - Sari, Fadlilah Indira; Buditjahjanto, I Gusti Putu Asto; Nurlaela, Luthfiyah; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2020)
Education is a conscious and planned effort to create an atmosphere of learning and learning process so students actively develop their potential. The development of information technology has led to the emergence of various learning model innovations in the world of education. Innovative learning models themselves emerge as alternative solutions to overcome various obstacles in traditional methods. One application of information technology in education is the development of e-learning. Therefore, the researchers offer an alternative to the limitations of learning resources so that it is more interesting for students to learn the material taught by using e-learning based on video tutorials needed in taking a computer-aided fashion design course. This research is an experimental research with a quantitative approach. The sampling technique used in this study is Stratified random sampling. Data collection techniques consist of: (1) tests; (2) interview; (3) observation; (4) questionnaire or questionnaire; and (5) documentary films. The results of the study concluded that the cognitive, affective, and psychomotor learning outcomes of students who used the hybrid learning model were significantly higher than students who used the direct learning model.